PENGETAHUAN DAN POLA MAKAN DENGAN STATUS GIZI REMAJA DI PONDOK PESANTREN NAHDLATUL ULUM SOREANG MAROS - Musyayyib, Rahmatullah; Hartono, Rudy; Pakhri, Asmaruddin (Media Kesehatan Politeknik Kesehatan Makassar, 2017)
Teenagers need higher nutrients than adults in adolescents, there is an increase in physical growth and significant body development. Changes in lifestyle and eating habits of adolescents affect their intake and nutritional needs.This study aims to determine the relationship of knowledge and diet with the nutritional status of adolescents at the Nahdlatul Ulum Islamic Boarding School Soreang Maros.This research is an analytical study with cross sectional survey design. The subject in this study were adolescents at the Nahdlatul Ulum Islamic Boarding School in Soreang Maros, Maros Regency, amount to 134 people. The nutritional knowledge of the subject was obtained through interviews using a questionnaire. The subject diet was obtained through interviews using Food Frequency Quesionarrie (FFQ). Nutritional status (BMI / U) of the sample is obtained from the results of measurements of body weight and height. To find out the relationship between variables of knowledge and diet with nutritional status, chi square test was conducted using SPSS program. Data is presented in the form of frequency distribution and narrative tables.The results of the study show that subject knowledge is 73.1% good and 26.7% less. The subject diet was 53.10% less and 47.0% good. The nutritional status of the subject was 94.8 good and 5.2% more. The results of statistical tests between variables showed no relationship between knowledge and diet and there was no relationship between knowledge and nutritional status and there was a relationship between diet and nutritional status. Keywords     : Nutrition Knowledge, Diet,Nutritional Status